CBD vs. Casino : how Brazil's biggest retailer fought a French governance takeover - and lost - Shein, James B., 1942- ([London] : SAGE, 2016)
Brazilian retail markets had been a tempting arena for growth-minded companies since the country instituted democratic reforms in the 1980s. To raise capital for continued expansion, Abilio Diniz, the billionaire chairman of Brazil's number-one retailer Companhia Brasileira de Distribuic'ao (CBD), entered a long-term agreement in 2005 to transfer control of the retail empire to the CEO of the French retailer Casino Guichard-Perrachon SA in 2012. This case examines why the deal failed.
Originally Published in: Shein, J. (2015). CBD vs. Casino: How Brazil's Biggest Retailer Fought a French Governance Takeover-and Lost. 5-115-003. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Diniz, Abilio dos Santos; Companhia Brasil de Distribuic'ao.; Casino (Firm); Carrefour (Market chain); Business ethics -- Case studies; Corporate governance -- Case studies; International business enterprises -- Case studies